Residents' involvement in city brand co-creation and their perceptions of city brand identity: a case study in Porto - Casais, Beatriz Graça Luz (2019)
This study discusses residents' involvement in the co-creation of a city brand, their perceptions about brand identity and authenticity and the fit with their sense of place. The city of Porto, Portugal, was chosen as a case study, since a new city brand was created in September 2014. The authors analysed the descriptive book explaining the strategy of the city brand created. In order to understand residents' involvement, an interview with the head of communication of Porto City Council was conducted. Then, a focus group was developed with Porto residents from different parts of the city. The focus group gathered the residents' perception about the brand created and their opinion about authenticity and place identity. Results indicate that, despite being partly involved in the creation of Porto city logo, residents would like to have contributed to the recognised place marketing strategy in a more active way. Citizens agree that the brand fits with their sense of place identity, but consider that the strategy is designed to attract tourists and not to reinforce citizens' place attachment. The failure of internal place marketing is discussed in the paper and some recommendations for public policy are presented.